The effect of different surface treatments on light transmittance of nano-hybrid and polymer-infiltrated ceramics - Işıl Çekiç Nagaş; Ferhan Eğilmez; Gülfem Ergün; Pekka Vallittu; Lippo Lassila (Gazi University, 2017)
Objective: The aim of this study was to evaluate the effect of different surface treatments on the light transmittance of three different esthetic computer-aided design/computer-aided manufacturing (CAD/CAM) materials (Vita Enamic, Cerasmart, Lava Ultimate). Materials and Method: Thirty-five specimens from each of nano-hybrid and polymer-infiltrated ceramic network-structured CAD/CAM blocks (Vita Enamic, Lava Ultimate, Cerasmart) were prepared (n=105). Then the specimens were divided into 5 sub-groups according to the applied surface treatment (n=7/group). Group 1: Sandpaper (#1000 and #4000 grit SiC paper) as control, Group 2: Aluminium oxide finishing and polishing disc (Sof-Lex Disk), Group 3: Diamond filled polishing paste (Diapolisher Paste), Group 4: Diamond polishing disc (Diacomp Plus Twist) and Group 5: Silicone rubber polisher (Polydentia). Following finishing and polishing procedures of the specimens, the light transmittance of the specimens under plasma arc light-curing unit was measured by using a hand-held radiometer. Statistical significance was determined using two-way ANOVA and Tukey post-hoc tests (α=0.05). Results: Regarding the main effects, significant difference was observed between the light transmittance values of the CAD/CAM hybrid ceramic materials (p<0.05): Cerasmart (83.3%±3.7), Vita Enamic (80.5%±5.3), and Lava Ultimate (76.5%±4.9). Different surface finishing and polishing procedures had no significant effect on the light transmittance values (p=0.608). However, the material and procedure interaction revealed a significant effect on the light transmittance values (p<0.05). Conclusion: Application of surface finishing and polishing procedures might affect the light transmission property of nano-hybrid and polymer infiltrated ceramic network structured CAD/CAM blocks.